A Common Fixed Point Theorem for Weakly Compatible Mappings in Compact Metric Spaces Satisfying an Implicit Relation - Aliouche, Abdelkrim (Sarajevo Journal of Mathematics, 2024)
We prove a common fixed point Theorem for four mappings in compact metric spaces satisfying an implicit relation using the concept of weak compatibility without decreasing assumption which generalizes Theorem 1 of V. Popa [9]. 2000 Mathematics Subject Classification. 54H25, 47H10